Kinetics of Vinyl Polymerization of Methyl Methacrylate Initiated by Ce(IV)-Vanillin Redox System - M. Palanivelu; K. E. N. Nalla Mohamed; T. Hidayathulla Khan; M. Prem Nawaz (E-Journal of Chemistry)
The kinetics of polymerization of methyl methacrylate initiated by Ce(IV)-Vanillin redox system was studied in aqueous solution of sulfuric acid at 40°C. The rate of polymerization (Rp) and the reaction orders with respect to monomer, initiator and ligand have been determined and found to be 1.5, 0.5 and 0.5 respectively. The effect of concentration of sulfuric acid on the polymerization was also studied. The rate of polymerization was found to increase with increasing temperature 30–60°C and decreases at higher temperature (>60°C). The overall activation energy (Ea) was found to be 36.7 kJ/mol. A suitable kinetic scheme has been proposed.